The Relationship Between Healthy Behavior and Longevity Among Older Adults in Betiting Village, Gresik Regency - Moelyanto, Adam (Fakultas Kedokteran Universitas Lampung, 2025)
The increasing proportion of older adults in Indonesia highlights the importance of maintaining health and quality of life in later years. One of the key determinants of longevity is the adoption of healthy behaviors in daily life. Healthy behavior includes regular physical activity, balanced nutrition, adequate sleep, and adherence to clean and healthy lifestyle practices. This study aims to analyze the relationship between healthy behavior and longevity among older adults in Betiting Village, Gresik Regency. This observational analytic study employed a cross-sectional design. A total of 74 older adults were selected through stratified random sampling. Healthy behavior was assessed using the Lifestyle Medicine Health Behavior Scale (LMHB), while longevity was measured based on the respondents’ chronological age. Data were analyzed using Spearman’s correlation test. The results showed a significant positive relationship between healthy behavior and longevity (r = 0.498; p < 0.001). These findings indicate that older adults who engage in healthier behaviors tend to achieve longer lifespans than those with poorer health habits. This study underscores the importance of promoting healthy behavior as a major determinant of longevity in older populations. Support from families and communities is essential to encourage older adults to maintain healthy routines and achieve a better quality of life.